Diagnosis delays in the UK according to pre or postmigration acquisition of HIV. (1st March 2022) - Stirrup, Oliver; Tostevin, Anna; Ragonnet-Cronin, Manon; Volz, Erik; Burns, Fiona; Delpech, Valerie; Dunn, David
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: The aim of this study was to evaluate whether infection occurred pre or postmigration and the associated diagnosis delay in migrants diagnosed with HIV in the UK. Design: We analyzed a cohort of individuals diagnosed with HIV in the UK in 2014–2016 born in Africa or elsewhere in Europe. Inclusion criteria were arrival within 15 years before diagnosis, availability of HIV pol sequence, and viral subtype shared by at least 10 individuals. Methods: We examined phylogenies for evidence of infection after entry into the UK and incorporated this information into a Bayesian analysis of timing of infection using biomarkers of CD4 + cell count, avidity assays, proportion of ambiguous nucleotides in viral sequences, and last negative test dates where available. Results: One thousand, two hundred and fifty-six individuals were included. The final model indicated that HIV was acquired postmigration for most MSM born in Europe (posterior expectation 65%, 95% credibility interval 64–67%) or Africa (65%, 62–69%), whereas a minority (20–30%) of men and women with heterosexual transmission acquired HIV postmigration. Estimated diagnosis delays were lower for MSM than for those with heterosexual transmission, and were lower for those with postmigration infection across all subgroups. For MSM acquiring HIV postmigration, the estimated mean time to diagnosis was less than one year, but for those who acquired HIV premigration, the mean time from infection to diagnosis was more than five years for all subgroups. Conclusion: Acquisition of HIV postmigration is common, particularly among MSM, calling for prevention efforts aimed at migrant communities. Delays in diagnosis reinforce the need for targeted testing initiatives.